Lombez, C. (Ed.). (2021). Circulations littéraires. Transferts et traductions dans l’Europe en guerre (1939-1945). Presses Universitaires François-Rabelais. (pp. 245): Book Review - Delodder, Maxim (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
Book review